Field-induced slow magnetic relaxation in the first Dy(iii)-centered 12-metallacrown-4 double-decker - Athanasopoulou, Angeliki A.; Baldovi, Jose J.; Carrella, Luca M.; Rentschler, Eva (Dalton Transactions, 2019)
The reaction of Dy(O2CMe)3·xH2O and Ga(NO3)3·xH2O led to the isolation of (nBu4N)[GaIII8DyIII(OH)4(shi)8] (1). The compound possesses a unique chemical structure enclosing the central magnetic DyIII ion between diamagnetic GaIII-based metallacrown 12-MC-4 ligands. The double-decker complex exhibits field-induced single-molecule magnet (SMM) behaviour with an effective energy barrier (Ueff) of 39 K (27.1 cm-1). Consistent with the observed slow relaxation of magnetization, theoretical calculations suggest a ground state mainly determined by |±11/2> in the easy axis direction.
CRIS-Team Scopus Importer:2023-03-27